The core concepts of physiology : a new paradigm for teaching physiology - Michael, Joel A., 1940-; Cliff, William; McFarland, Jenny; Modell, Harold I.; Wright, Ann (Springer, 2017)
"This book offers physiology teachers a new approach to teaching their subject that will lead to increased student understanding and retention of the most important ideas. By integrating the core concepts of physiology into individual courses and across the entire curriculum, it provides students with tools that will help them learn more easily and fully understand the physiology content they are asked to learn. The authors present examples of how the core concepts can be used to teach individual topics, design learning resources, assess student understanding, and structure a physiology curriculum"-Resumé vydavatel
"Published on behalf of The American Physiological Society by Springer."
Keywords: fyziologie člověka; patologická fyziologie; human physiology; pathological physiology; elektronické knihy; monografie; electronic books; monographs